Factors Influencing Islamic Education: Government Policy, Principals and Teachers - Taufik Abdillah Syukur; Tania Putri Anhary; Habel S.J. Rieuwpassa; Goldwag Megan; Sun Limei (al-fikrah: Jurnal Manajemen Pendidikan, 2023)
Education is something that is familiar in life, and cannot be separated from the human soul, education is a big benchmark for every ability possessed by a person, where everyone takes education in order to achieve their goals in the future. Likewise with Islamic education, Islamic education also contains various matters concerning the religion of Islam, then Islamic education also becomes a reference for every Muslim in the world to assist them in solving every subject matter regarding religion that occurs in everyday life. Education is also an extraordinary thing to elevate one's level of life. This research also discusses the factors that will influence the policies of school principals, teachers and also the government. The purpose of this research is to find out what are the factors in Islamic education that can influence government policies, school principals, and teachers. The research method used is a method with descriptive qualitative understanding by interviewing one of the elementary school teachers in the area where the researcher lives, by asking several questions. Researchers ask several questions related to the subject matter raised. Interviews were conducted continuously until the answers were sufficient to describe the actual situation. The results of this study are that there are many influences of Islamic education that arise in government policies, principals and teachers.